2020
DOI: 10.1038/s41467-020-15671-5
|View full text |Cite
|
Sign up to set email alerts
|

Computational analysis of pathological images enables a better diagnosis of TFE3 Xp11.2 translocation renal cell carcinoma

Abstract: TFE3 Xp11.2 translocation renal cell carcinoma (TFE3-RCC) generally progresses more aggressively compared with other RCC subtypes, but it is challenging to diagnose TFE3-RCC by traditional visual inspection of pathological images. In this study, we collect hematoxylin and eosin-stained histopathology whole-slide images of 74 TFE3-RCC cases (the largest cohort to date) and 74 clear cell RCC cases (ccRCC, the most common RCC subtype) with matched gender and tumor grade. An automatic computational pipeline is imp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
41
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 60 publications
(41 citation statements)
references
References 45 publications
0
41
0
Order By: Relevance
“…Previous studies have shown that image features and machine learning techniques can discern subtle differences that are not readily noticeable to pathologists between tissues from patients with different disease subtypes, cancer grades, and survival; 28 , 29 , 30 , 31 here, we further extend the scope to predict response to NAC in MIBC. Spatial heterogeneity is a hallmark of cancer, and features of the tumor microenvironment (TME) may drive tumor responses to specific therapies.…”
Section: Discussionmentioning
confidence: 98%
“…Previous studies have shown that image features and machine learning techniques can discern subtle differences that are not readily noticeable to pathologists between tissues from patients with different disease subtypes, cancer grades, and survival; 28 , 29 , 30 , 31 here, we further extend the scope to predict response to NAC in MIBC. Spatial heterogeneity is a hallmark of cancer, and features of the tumor microenvironment (TME) may drive tumor responses to specific therapies.…”
Section: Discussionmentioning
confidence: 98%
“…In this study, we used a 5-fold cross-validation to assess the prediction performance of the model because it was the most commonly used method for machine learning-based medical problem exploration (33)(34)(35)(36)(37). Specifically, the available training set was divided into five roughly equal-sized subsets: the training set and the validation (or internal validation) set.…”
Section: Validationmentioning
confidence: 99%
“…In view of the color variations between different institutions, before feature extraction we normalized the color appearance of the images using a structure-preserving color normalization algorithm (37). We manually labeled tumor and non-tumor regions in whole-slide images and extracted a total of 150 patient-level image features within the tumor regions using a histopathological image analysis pipeline we previously developed in our lab (38). The feature extraction pipeline is comprised of three steps: segmenting cell nuclei, extracting celllevel features, and summarizing cell-level features into patientlevel features.…”
Section: Extraction Of Quantitative Features From Whole-slide Imagesmentioning
confidence: 99%